Dual Authority Representation: The Counter-Mainstream Text and Audience Responses – Al-Ghafouri’s Texts Addressed to the Prophet (PBUH) as a Model. Every Creative Work Is Authority, and Every Authority Is a Transgression - Abdullah Al-Mahjari, Mohamed (El Omda in Linguistics and Discourse Analysis, 2019)
Abstract: This study tackles the representation of the dual power of both the text that is addressed to an audience as power and the audiences’ responses as a parallel power that interact with the text and resist it. The study tackles the creative product and investigate the power representation through its motives and manifestations. The study analyzes a text entitled ‘In the day of your Birth: ‘Mohamed, Lift the Blockade on my city’ by Marwan al-Ghafouri. It identify and analyze the audience responses and expose their negotiations with the power of the writer’s text. It argues that these responses form a sort of power that affect the writer position and its writings as well as the other responses of the readers. On the other hand, the study argues that the audiences’ responses influence the position of the writer and his writings as well as the nonaligned responses through its ways of attractions.